From Allocation to Impact: Evaluating the Effectiveness of School Budget Models in Indonesia - Pantas, Pribawa E; fitriana, Destri (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
The management of education funds in Indonesia faces serious problems in terms of distribution and transparency. One of the impacts caused by this problem is the inequality that occurs in various regions, especially in underdeveloped and remote areas. This study aims to analyze the effectiveness of education financing mechanisms in schools. A qualitative approach is used in this study with a case study technique in schools in Indonesia. Data collection techniques use interview techniques, documentation and education report data. The results of the study indicate that the effectiveness of the education budget needs to carry out three functions of education financing, namely suitability, on target, and transparency. The third function also opens the tap for local elements and communities in the school environment to play a role in more optimal supervision efforts